ISU CHILDFREE DALAM PERSPEKTIF AL-QUR’AN “Analisis Tafsir Tematik Konseptual” - Muthohiroh, Indah; Arifin, Achmad Zainul (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2023)
Childfree is a decision not to have children. Childfree itself is considered a common thing on the European continent, in contrast to the case in Indonesia, which is still the pros and cons. This issue deserves to be researched because not a few people, especially in Indonesia, apply it in their lives. However, in this case the author is interested in researching more about childfree in the perspective of the Qur'an.This study uses descriptive-analysis, which is to receive detailed information by explaining about childfree, while this research is qualitative, by using documentation using library research techniques, namely by using data sourced from books and research. which is relevant to the discussion, while in the study of the Qur'an and Tafsir the author uses the Thematic Tafsir method, which is a way of interpreting the Qur'an by taking a certain theme and then collecting verses related to the theme, so as to form a complete idea. In drawing conclusions, the author uses the documentation method, namely by finding and collecting sources of material or literature such as books of interpretation or books that discuss childfree. The results of this thesis research, show that childfree is a decision not to have children. This concept is closely related to women who directly experience the process. In the Qur'an and hadith, there are many explanations related to the bad treatment of the Jahiliyyah Arab community towards women. Until this concept exists as a form of recognition that women can also play an important role in various fields. If having children is only to please people's views without thinking about the situation and future of the child, then it is not good for the household especially children and the roles and responsibilities of parents will be considered trivial.